Effect of Terminalia chebula Retz extract on blood coagulation parameters of mouse - Roohullah Arifzai; Jafar Vatandoost; Eisa Kohan-Baghkheirati; Toktam Hajjar (Institue of Medicinal Plants, ACECR, 2023)
Background: Coagulation disorders involve a wide range of medical issues resulting from a deficiency or absence of certain coagulation factors in plasma. While existing therapies exist, herbal medicine presents an alternative and effective approach for treating bleeding disorders. Terminalia chebula Retz has been reported for its efficacy in ethnobotanical practices for bleeding stopping. Objective:  The in vivo effectiveness of T. chebula Retz as an herbal medicine was examined using mice. Methods: Thirty-two mice were randomly divided into three treatment groups (n = 8) receiving different doses (2000, 1000, and 500 mg/kg/day), along with a negative control group. Blood samples were collected from the tail and heart on the 16th and 18th day of treatment, respectively, to determine coagulation parameters, including bleeding time (BT), clotting time (CT), prothrombin time (PT), activated partial thromboplastin time (aPTT), and platelet count (PLT). Results: The results demonstrated the effectiveness of T. chebula hydroalcoholic extract in promoting primary and secondary homeostasis. There was a significant decrease in bleeding time (70 %) and a substantial increase in platelet count (80 %). Moreover, the extract led to a notable reduction in clotting time (80 %) indicating its impact on primary homeostasis through platelet aggregation. Additionally, T. chebula extract shortened the coagulation time in both PT (70 %) and aPTT (20 %) tests, reflecting its influence on the extrinsic and intrinsic pathways of secondary hemostatic parameters, respectively. Conclusion: In conclusion, the optimal concentration (500 mg/kg/day) of hydroalcoholic extract of T. chebula appears to be effective in promoting blood coagulation through primary and secondary homeostasis.